Partial AZFc duplications not deletions are associated with male infertility in the Yi population of Yunnan Province, China - Ye, Jun-jie (Zhejiang University Press, 2013)

(untitled)
Objective: There are many reports on associations between spermatogenesis and partial azoospermia factor c (AZFc) deletions as well as duplications; however, results are conflicting, possibly due to differences in methodology and ethnic background. The purpose of this study is to investigate the association of AZFc polymorphisms and male infertility in the Yi ethnic population, residents within Yunnan Province, China. Methods: A total of 224 infertile patients and 153 fertile subjects were selected in the Yi ethnic population. The study was performed by sequence-tagged site plus/minus (STS+/−) analysis followed by gene dosage and gene copy definition analysis. Y haplotypes of 215 cases and 115 controls were defined by 12 binary markers using single nucleotide polymorphism on Y chromosome (Y-SNP) multiplex assays based on single base primer extension technology. Results: The distribution of Y haplotypes was not significantly different between the case and control groups. The frequencies of both gr/gr (7.6% vs. 8.5%) and b2/b3 (6.3% vs. 8.5%) deletions do not show significant differences. Similarly, single nucleotide variant (SNV) analysis shows no significant difference of gene copy definition between the cases and controls. However, the frequency of partial duplications in the infertile group (4.0%) is significantly higher than that in the control group (0.7%). Further, we found a case with sY1206 deletion which had two CDY1 copies but removed half of DAZ genes. Conclusions: Our results show that male infertility is associated with partial AZFc duplications, but neither gr/gr nor b2/b3 deletions, suggesting that partial AZFc duplications rather than deletions are risk factors for male infertility in Chinese-Yi population.